Genetic line influences pig growth rate responses to vaccination for porcine circovirus type 2 - Potter, M. L.; Tokach, Lisa M.; Dritz, Steven S.; Henry, Steven C.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Rowland, Raymond R. R.; Hesse, Richard A.; Oberst, Richard D.; Anderson, Joseph; et al. (My University, 2012)
Objectives: To compare the effects of porcine circovirus type 2 (PCV2) vaccination on growth rate, backfat depth, and loin depth of pigs in a high-health herd which contained different genetic lines. Materials and methods: A total of 454 pigs (20.6 ± 1.98 days of age; 6.1 ± 1.27 kg body weight) were used in a 130-day randomized controlled field trial. Genetic designations were A×A (Duroc line), B×B (synthetic White Pietrain line), A×B, and B×A. Pigs were randomly assigned to vaccination treatments (Vaccinated or nonvaccinated Control) within litter by gender (boar or gilt). Vaccinated pigs received two doses of a PCV2 vaccine at 3 and 5 weeks of age. Serum samples were collected and pigs were individually weighed on Days 0 (weaning), 40, and 130 to determine PCV2 viral load, antibody levels, and average daily gain (ADG). Data were analyzed from 417 pigs with complete growth records. Results: The greater ADG from Day 0 to Day 130 for Vaccinated pigs depended on the genetic line (genetic line-by-vaccination interaction; P < .05). The mean weight difference between Vaccinated and Control pigs was almost four times greater in the A×A pigs than in the B×B pigs on Day 130. On average, compared with Control pigs, Vaccinated pigs had lower serum PCV2 viral load levels on Days 40 and 130 (P < .001). Implications: Pig genetic line affects growth rate response to PCV2 vaccination and should be considered a risk factor for circoviral disease expression.
Keywords: Swine; Genetic line; Growth; Porcine circovirus type 2; Vaccine